Constitutional implications of implementing the presidential threshold on the presidential system in Indonesian constitutional practice - Suci Ramadhani; Widia Oktavia Ramadhani; Rusia Azuba; Moh. Imam Gusthomi (Priviet Social Sciences Journal, 2026)
This study analyzes the constitutional implications of implementing the presidential threshold in Indonesia’s presidential system, particularly regarding presidential legitimacy, the separation of powers, political participation, and governmental stability. The main problem is whether the presidential threshold strengthens the presidential system or creates constitutional tensions within Indonesia’s democratic and multiparty frameworks. This study aims to examine its implementation in electoral practice, assess its consistency with presidentialism, and evaluate its impact on democratic representation. This study uses a normative legal method with statutory, conceptual, historical, and case approaches. The novelty of this study lies in viewing the presidential threshold as a constitutional issue rather than merely an electoral technical requirement. The findings show that the presidential threshold produces ambivalent effects: it may support short-term stability through early coalition-building and legislative support, but it may also weaken substantive democracy by limiting political participation, narrowing voter choices, encouraging pragmatic coalitions, and making presidential nomination dependent on parliamentary configurations.